Physical training alters the reactions of haemostasis system to hypoxia - I. I. Shakhmatov; O. V. Alekseyeva; V. I. Kiselyov (Бюллетень сибирской медицины, 2010)
Physical pretraining of 102 Wistar rats during 30 days altered the reactions of haemostasis system to one-day hypobaric hypoxia. Decreased level of thrombinemia, ameliorated platelete, and plasma hаemostasis, increased anticoagulation, and fibrinolytic activity were observed. These changes were more pronounced in the experimental group of animals having experienced intensive physical training.